IDENTIFYING THE DRIVERS FOR GREEN SUPPLY CHAIN IMPLEMENTATION - Mawadh Atif Bana; Ahmed Attia (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Green supply chain management required use of environmentally friendly raw materials that transformed into products that used for considerable period without caused damage to the environment. The raw material and inputs used in production of goods and reused, recycled at end of the product life cycle thus made the process environmentally sustainable. Green supply chain management (GSCM) was quite new topic in operations and supply chain management. This study aimed to explore key themes such as green operations management and manufacturing, reverse logistics and waste management. The population was selected mostly included Saudi Arabian national followed by expatriate workers from countries such as India, Philippines and Pakistan who worked in the supply chain function in various companies in Kingdom of Saudi Arabia. The survey was provided to 100 potential respondents which only 44 real respondents had involved in this study. The data was collected from Aramco company employer in Saudi Arabia that looks into government compliance and provided result and conclusions on the factors that motivated shift towards green supply chain management.